Strategic risk management in some large Colombian private companies (2020)
Strategic risk management is a continuous activity that identifies the events that affect the capacity of an organization in creating value and which can hinder the attainment of its strategic goals. This activity requires a framework that defines the structure, roles, responsibilities, policies, risk appetite and the integration with strategy and organizational management. The main goal of this article is to describe how some large Colombian private companies do their strategic risk management. Qualitative methods were used and five semi structured interviews were conducted with leaders in strategic risk management from large energy, brewing, food and soft drink companies. One of the main findings was the importance of an integrated strategic and risk managment in the companies, so as to mitigate the impact of negative events and take advantage of the timely identification of opportunities. It was also found that thorough qualitative and quantitative information available in the analysis of risk helps to reduce existing uncertainty. From the knowledge of these processes, this article proposes a starting point for organizations that wish to implement strategic risk management as a mobilizer for the achievement of business objectives.